Where do we invest money to implement active learning on caries detection? An economic evaluation - Jhandira Daibelis Yampa VARGAS; Thais Gomes MACHADO; Gabriele OLIVEIRA; José Carlos Pettorossi IMPARATO; Daniela Prócida RAGGIO; Fausto Medeiros MENDES; Mariana Minatel BRAGA (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract This trial-based economic evaluation aimed to estimate the incremental cost of implementing an active learning strategy (theoretical-practical workshop) to substitute the didactic lecture as the sole method for students training in caries detection. We also provided a budget impact analysis and explored the composition of costs related to the activity. Data from the coordinating centre of a multicentre randomized and controlled study (IuSTC01) was analyzed as the first part of our main economic analysis plan. The perspective of the educational provider (the institution implementing the activity) was considered, and an immediate time horizon was adopted. All used resources were valued in Brazilian Real by adopting a microcosting strategy. Costs for each strategy were estimated and converted into international dollars. The incremental Cost per student and the total cost of implementing the complete teaching strategy for 80 students were calculated. Monte Carlo simulations were used to estimate the uncertainties. The incremental Cost estimated for the workshop implementation would be $7.93 per student (interquartile range (IQR): $7.8-8.1), and the total cost of the teaching activity would be $684 (IQR:672-696). The laboratory training comprised more than 50% of the total amount spent, and a higher percentage of this value was related to human resources costs (72%). Saving 40% of the costs could be expected for the next rounds of activities in the institution, assuming no need for additional preparation of didactic materials and tutor training. A modest incremental cost per student and an acceptable organizational budget impact should be expected for the institution when including active learning training in caries detection for undergraduate students, mainly related to the human resources involved.